(untitled) (Письма в ЭЧАЯ, 2024)
Most neutron deficient α-emitters are known to be of great relevance to the astrophysical rapid neutron capture process in superheavy nuclei. Thus, in the present work, the decay properties of the newly observed superheavy nuclei with Z=102 ie ^249No isotope from the α-decay of ^253Rf is theoretically investigated using the relativistic mean field (RMF) framework and the NL3^* parameter set within the preformed cluster-decay model (PCM). The α-decay chain of ^255Rf is also considered. The RMF densities are folded with the R3Y nucleon-nucleon (NN) potential to deduce the nuclear interaction potential between the decaying fragments. A complete understanding of the penetration of an α-particle across the nuclear Coulomb barrier gives outstanding credence to the assumptions of quantum mechanics. The presence of shell/sub-shell closure is indicated by the formation of peaks along the decay chain and was found to alter the conventional scaling factor observed earlier in the results of the PCM. The calculated half-lives are in close agreement with the recent experimental measurement.